Analysis of thermal comfort, energy consumption, and CO2 reduction of indoor space according to the type of local heating under winter rest conditions. (1st April 2023) - Lee, Minjung; Ham, Jeonggyun; Lee, Jeong-Won; Cho, Honghyun
Abstract: In this study, the thermal comfort of indoor spaces while resting under winter indoor conditions was evaluated by analyzing the bio-signals of the human body according to the seat type, and then energy use and CO2 reduction were calculated for space heating. While resting during the winter, the use of a HH (hot-water heating) seat appears to have provided a stable resting environment because the θ-wave of the subjects was activated. In addition, the subjective survey analysis results showed that the use of the EH (electric heating) seat and HH seat provided the subjects with an appropriate resting environment and observed a high concentration when the EH seat was used. When the EH and HH seats were used at an indoor temperature of 22.5 °C, provided the same thermal comfort in winter, the energy consumption decreased by 2060.6 and 1231.2 MJ, respectively, compared to the indoor temperature set to 25.4 °C. Accordingly, coal consumption decreased by 8.9% and 5.3%, respectively. Besides, the CO2 and SO2 emissions decreased by up to 193.1 and 1.07 kg, respectively. It was confirmed that local heating while resting in an indoor space can reduce the heating load and energy consumption and improve the thermal comfort of the occupant. Highlights: Thermal comfort of indoor space while resting was evaluated by using bio-signals. Hot water heating seat provided a stable and comfort resting environment. When the electric and hot water heating seat were used, the energy consumption decreased by 2060.6 and 1231.2 MJ. Local heating can reduce energy consumption as well as improve thermal comfort.